Innovation networks in the advanced medical equipment industry: supporting regional digital health systems from a local–national perspective - Feng Hu; Huijie Yang; Liping Qiu; Xiaoping Wang; Zhimin Ren; Shaobin Wei; Haiyan Zhou; Yufeng Chen; Hao Hu (Frontiers in Public Health, 2025)
This study investigates the spatial structure and influencing factors of the innovation network in the advanced medical equipment and device manufacturing industry in the Yangtze River Delta (YRD). This industry is crucial to public health system resilience and regional industrial upgrading. Drawing on joint patent data from the IncoPat Global Patent Database covering the period 2005–2024, the study constructs innovation networks and conducts comparative analyses from both national and regional perspectives using social network analysis and geodetector methods. The findings reveal that: (1) At the national level, the innovation network has gradually expanded but remains sparse, characterized by a “core–periphery” structure dominated by Beijing and Shanghai. Urban participation in central and western China is limited. Short-term objectives often drive industry–university–research collaborations, and collaborations in basic research among academic institutions remain insufficient. (2) In contrast, the YRD region has formed a denser, polycentric network, with Shanghai as the primary hub and Nanjing and Suzhou as key secondary centers. Local enterprises exhibit strong incentives to engage in collaborative innovation within industry–university–research frameworks. (3) Geodetector analyses indicate that economic development, technological capability, and government policy support are major drivers of network formation, while infrastructure quality plays a crucial enabling role. The relative importance of these factors varies between national and regional levels. These results provide empirical evidence to inform regional innovation strategies and targeted policy design for strengthening collaboration in the advanced medical equipment industry.